2021
DOI: 10.3390/molecules26154598
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of Liquid Chromatography-Tandem Mass Spectrometry Methods for the Quantification of Cefquinome, Ceftiofur, and Desfuroylceftiofuracetamide in Porcine Feces with Emphasis on Analyte Stability

Abstract: Cefquinome and ceftiofur are β-lactam antibiotics used for the treatment of bacterial infections in swine. Although these antimicrobials are administered intramuscularly, the exposure of the gut microbiota to these cephalosporins is not well described. This exposure can contribute to the emergence and spread of antimicrobials in the environment and to the possible spread of antimicrobial resistance genes. To assess the impact of drug administration on the intestinal excretion of these antimicrobials it is esse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Feces were sampled in a sterile plastic cup after non-invasive rectal stimulation before the administration of ceftiofur and at 4, 6.5, 10, 23, 28, 31, 33.5, 46.5, 51, 54 and 57 h after the start of the treatment. It has been previously observed that the fecal microbiota can rapidly degrade the β-lactam ring of ceftiofur, its related metabolites and cefquinome [37,74]. Therefore, immediately after sampling, 500 µL of a tazobactam solution (8 mg•L −1 ) in water was added to an aliquot of 0.5 g sampled feces.…”
Section: Animals and Test Article Administrationmentioning
confidence: 99%
See 2 more Smart Citations
“…Feces were sampled in a sterile plastic cup after non-invasive rectal stimulation before the administration of ceftiofur and at 4, 6.5, 10, 23, 28, 31, 33.5, 46.5, 51, 54 and 57 h after the start of the treatment. It has been previously observed that the fecal microbiota can rapidly degrade the β-lactam ring of ceftiofur, its related metabolites and cefquinome [37,74]. Therefore, immediately after sampling, 500 µL of a tazobactam solution (8 mg•L −1 ) in water was added to an aliquot of 0.5 g sampled feces.…”
Section: Animals and Test Article Administrationmentioning
confidence: 99%
“…The fecal concentration of ceftiofur, desfuroylceftiofuracetamide and cefquinome was determined using (U)HPLC-MS/MS methods, as previously described [37]. The LOQ was 5 ng•g −1 for ceftiofur, 30 ng•g −1 for desfuroylceftiofuracetamide and 5 ng•g −1 for cefquinome.…”
Section: Antibiotic Fecal Measurementmentioning
confidence: 99%
See 1 more Smart Citation
“…Rapid and efficient detection of drug residues in animal-derived food remains a key issue. Several residue detection methods have been reported, such as chromatographic methods [ 7 , 8 ], microbiological methods [ 9 , 10 , 11 ], and enzyme-linked immunosorbent assays (ELISA) [ 12 , 13 , 14 ]. Microbiological methods in residue screening on high throughput showed good performance but lack specificity and sensitivity.…”
Section: Introductionmentioning
confidence: 99%